2013
DOI: 10.1371/journal.pone.0058303
|View full text |Cite
|
Sign up to set email alerts
|

Children’s Medicines in Tanzania: A National Survey of Administration Practices and Preferences

Abstract: ObjectiveThe dearth of age-appropriate formulations of many medicines for children poses a major challenge to pediatric therapeutic practice, adherence, and health care delivery worldwide. We provide information on current administration practices of pediatric medicines and describe key stakeholder preferences for new formulation characteristics.Patients and MethodsWe surveyed children aged 6–12 years, parents/caregivers over age 18 with children under age 12, and healthcare workers in 10 regions of Tanzania t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 14 publications
3
34
0
Order By: Relevance
“…(Hermes Pharma, 2015). In contrast, Adams et al found that caregivers in Tanzania preferred pills to be swallowed intact, over chewable forms for school aged children (Adams et al, 2013). Notable differences in parental attitudes to orodispersible tablets have also been shown 290 between European countries (Valovirta and Scadding, 2009).…”
Section: Novel Dosage Formsmentioning
confidence: 96%
See 1 more Smart Citation
“…(Hermes Pharma, 2015). In contrast, Adams et al found that caregivers in Tanzania preferred pills to be swallowed intact, over chewable forms for school aged children (Adams et al, 2013). Notable differences in parental attitudes to orodispersible tablets have also been shown 290 between European countries (Valovirta and Scadding, 2009).…”
Section: Novel Dosage Formsmentioning
confidence: 96%
“…This can be 375 with the aim to improve acceptability, to facilitate administration, provide an appropriate dose, or a combination thereof. The nature, motives and consequences of these practices remains an under researched area; however, they have been widely reported amongst healthcare professionals (Skwierczynski and Conroy, 2008, Akram and Mullen, 2012, Richey et al, 2013 and as "coping strategies" among children and their caregivers (Hansen et al, 2008, Adams et al, 2013, Bryson, 380 2014.…”
Section: Practicesmentioning
confidence: 99%
“…The quantity of solid dosage forms was reported as a main problem when administering medicines to patients with HIV. [51] In a study by Adams et al, [52] the number of tablets that parents/caregivers and healthcare workers thought was acceptable for children in Tanzania to take as a single dose was reported. Typically, one tablet was felt to be most appropriate for children in early years of primary school (under 8 years) rising to two tablets in last years of primary school (9-12 years).…”
Section: Number Of Units Per Dose Administrationmentioning
confidence: 99%
“…However, this "ideal" situation is unlikely to be achieved in the short term, especially where resources are limited. Adams et al [47] noted the frequent need for preparation of drug formulations by crushing the pills made them so bitter to the point of causing vomiting in pediatric patients of rural and urban areas of Tanzania. A similar situation is found in Brazil, where the need to prepare extemporaneous formulations is still a commonplace reality, particularly in pediatrics and even more with respect to cardiovascular drugs [1,10,48,49].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a vehicle provides greater stability of the formulation [50]. Access to safe and palatable pediatric formulations and its rational use must remain a major goal in health development worldwide [47], and may have a substantial effect on child morbidity [28].…”
Section: Discussionmentioning
confidence: 99%